2010
DOI: 10.1111/j.1600-0528.2010.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Language and literacy relate to lack of children’s dental sealant use

Abstract: Mejia GC, Weintraub JA, Cheng NF, Grossman W, Han PZ, Phipps KR, Gansky SA. Language and literacy relate to lack of children’s dental sealant use. Community Dent Oral Epidemiol 2011; 39: 318–324. © 2010 John Wiley & Sons A/S Abstract Objectives:  This study aimed to determine the percent of California’s third grade public school children lacking sealants by child and family factors and to measure social disparities for lacking sealants. Methods:  The study analyzed data from the California Oral Health Needs As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…39 Low consent rates may be associated with low oral health literacy. Studies indicate that low sealant prevalence is associated with low health literacy 40 or low parental education, a predictor of health literacy. 41 Policies aimed at increasing oral health literacy among low-income caregivers could increase the number of high-risk children receiving sealants.…”
Section: Discussionmentioning
confidence: 99%
“…39 Low consent rates may be associated with low oral health literacy. Studies indicate that low sealant prevalence is associated with low health literacy 40 or low parental education, a predictor of health literacy. 41 Policies aimed at increasing oral health literacy among low-income caregivers could increase the number of high-risk children receiving sealants.…”
Section: Discussionmentioning
confidence: 99%
“…We classified education as a predisposing factor because of its strong association with health literacy (12,13), which in turn predicts higher sealant prevalence (10). This classification is also consistent with Andersen and Aday’s identification of education as a predisposing factor in their PEN model (17).…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with a child’s not having sealants include ability to pay for dental care (ie, low family income) (4); not having dental or health insurance (4); sociodemographic variables, including having parents who did not graduate high school (4); being of minority race/ethnicity (4); and low health literacy and low oral health literacy (10). A recent analysis found that parents’ functional health literacy and English being spoken at home were strong predictors of sealant prevalence among California school children (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The popularity of multiple imputation in dental epidemiology is growing. Most of the work attempts to estimate prevalence [Tellez et al, 2006;Ismail et al, 2008;Liao et al, 2010;Mejia et al, 2011;Newton et al, 2011], but there is also methodological work advocating a wider use of multiple imputation in dental research [Plutzer et al, 2010;Pahel et al, 2011].…”
mentioning
confidence: 99%